2018
DOI: 10.11591/edulearn.v12i3.7766
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Major Problems in Learning English Through Blog-based Class

Abstract: Students’ blog in PBIG Unilak have been used to promote English skills during these two years. This mixed method study aimed to identify and describes the major problems faced by the students during the implementation of blogging based class. This study based its data from 168 students who attended 5 different classes based-blog. Employing a total sampling technique, the students were invited to fill up online questionnaire and interview. However, only 161 feedbacks can be processed. The analysis in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Therefore, in their research, Hamuddin, et al, (2017, p.19) reminds the challenge beyond it "… the use of blog has given a massive impact in the learning process at PBIG FKIP Unilak, but then every new thing will have its own risk and challenge" that should be faced by the lecturers, students, and faculty together. However, in his latest research Hamuddin, et al (2018) mentioned "… the phenomena of cyberbullying among English students of PBIG Unilak who interact and communicate in the internet is also an interesting linguistic topic to be analyzed, on how these students of English as a foreign language trying to express their "feeling" and "thoughts" through blog as well as training their skill in writing into their blog to be something productive.…”
Section: Accordingmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, in their research, Hamuddin, et al, (2017, p.19) reminds the challenge beyond it "… the use of blog has given a massive impact in the learning process at PBIG FKIP Unilak, but then every new thing will have its own risk and challenge" that should be faced by the lecturers, students, and faculty together. However, in his latest research Hamuddin, et al (2018) mentioned "… the phenomena of cyberbullying among English students of PBIG Unilak who interact and communicate in the internet is also an interesting linguistic topic to be analyzed, on how these students of English as a foreign language trying to express their "feeling" and "thoughts" through blog as well as training their skill in writing into their blog to be something productive.…”
Section: Accordingmentioning
confidence: 99%
“…Teasley, M 2013Many others definition which came from the ten selected studies in this ongoing research, however, it is quite the same as the definitions and views above. Meanwhile, a slightly different perspective coming from Hamuddin et al (2018) who study cyberbullying among EFL students. In their study, they revealed that the cyberbullying phenomenon as "only an intention of playing with language as well as a language exaggeration from EFL students with their self-esteem resolutions when interacting on the online framework with their limited knowledge of English."…”
Section: Cyberbullying: the Definitionsmentioning
confidence: 99%
See 3 more Smart Citations